HLA Moleküllerinde Peptit Ligandlarının Kompleks Stabilitesine Olan Etkisinin Araştırılması - (:unkn) unknown (My University, 2018)
Hücre yüzey glikoproteinleri olan Temel Doku Uygunluk Kompleks (MHC) molekülleri yabancı antijenlere bağlanır ve onları uygun immüntanınma için antijen sunucu hücrelerin yüzeyindeki T lenfosit hücrelerine sunar. İlk olarak insanlarda lökosit hücrelerinde tanımlanmışoldukları için, aynı zamanda İnsan Lökosit Antijenleri (HLA) olarak da isimlendirilirler. Son zamanlarda peptit bazlı aşıların tasarlanmasıüzerine odaklanan çalışmalar, peptitin sitotoksik T hücre aracılı immün cevabı uyarma yeteneği olarak tanımlanan peptit immunojenitemekanizmasının anlaşılmasına olanak sağlamaktadır. Peptit immünojenisitesinin, peptit-HLA kompleksinin stabilitesi ile ilişkili olduğubilinmektedir. Bu çalışmada, AIFQSSMTK and QVPLRPMTYK peptitlerini bağlayan HLA-A*03:01 ve HLA-A*11:01 alellerinin stabilitesinintemel moleküler mekanizmalarını ortaya çıkarmak için moleküler dinamik simülasyonları gerçekleştirilmiştir ve ENCOM sunucusukullanılarak peptit rezidüleri üzerinde gerçekleştirilen tek nokta mutasyonlarının protein termostabilitesine olan tahmini etkisi araştırılmıştır.

Major Histocompatibility Complex (MHC) genes encode for the MHC molecule which is a cell surface glycoprotein that binds to foreign antigens and presents them to T lymphocyte cells on the surface of Antigen Presenting Cells (APCs) for appropriate immune recognition. Initially they have been identified in human leukocyte cells; hence they are also referred to as Humans Leukocyte Antigens (HLAs) in humans. Recently, studies focusing on designing peptide-based vaccines have allowed a better understanding of the mechanism of peptide immunogenicity, which is defined as the ability of a peptide to stimulate CTL mediated immune response. Peptide immunogenicity is also known to be related to the stability of peptide-HLA complex. Although there are several experimental methods in literature, molecular dynamics (MD) simulation methods have been widely used to understand structural, kinetic and thermodynamics properties of peptide-MHC complexes at the atomic level. In this study, the molecular mechanisms underlying the stability of HLA-A*03:01 and HLA-A*11:01 alleles bound to AIFQSSMTK and QVPLRPMTYK peptides was investigated by performing 50 ns long MD simulations of these peptide-HLA complexes using NAMD 2.9 software with CHARMM22 force field at 310 K. Root mean square deviation (RMSD), root mean square fluctuation (RMSF) and principal component (PCA) analysis were performed on the equilibrated MD simulation trajectories. According to RMSD analysis, in the presence of AIFQSSMTK peptide, HLA-A*03:01 allele is found to be more stable than HLA-A*11:01, while HLA-A*11:01 allele is found to be more stable than HLA-A*03:01 in the presence of QVPLRPMTYK peptide. Furthermore, according to PCA analysis, the differences between AIFQSSMTK peptide-HLA-A*03:01 and AIFQSSMTK peptide-HLA-A*11:01 complexes are observed in regions containing polymorphic residues (T9P, D90A, A152E, Q156L, E161D, P105S and R163T), while the differences between QVPLRPMTYK peptide-HLA-A*03:01 and QVPLRPMTYK peptide-HLA-A*11:01 complexes are detected in regions containing polymorphic residues (D90A, A152E, Q156L, E161D ve R163T). Additionally, estimated effects of single point mutations on the protein thermostability were investigated via ENCOM server, which uses Modeller to create mutant models. Our computational mutagenesis studies reveal that for HLA-A*03:01 and HLA-A*11:01 alleles bound to AIFQSSMTK peptide; P2, P3 and P9 are the three strongest stabilizing residues whereas residue P10 is the most stabilizing residue for HLA-A*03:01 and HLA-A*11:01 alleles bound to QVPLRPMTYK peptide. Moreover, for AIFQSSMTK peptide, the importance of the secondary anchor residue, P6, on stable binding is recognized while for QVPLRPMTYK peptide, the importance of P7 on stable binding is observed. As a result, it can be concluded that the computational approaches used in this study provides detailed information for the stability of HLA-A*03:01 and HLA-A*11:01 alleles bound to AIFQSSMTK and QVPLRPMTYK peptides and our methodology can be used to guide future experiments in this field.
Investigation of the Effect of Peptide Binding on the Complex Stability of HLA
Keywords: Biyoloji